Praziquantel treatment for Platynosomum species infection of a domestic cat on St Kitts, West Indies. Issue 1 (15th June 2015) - Shell, Linda; Ketzis, Jennifer; Hall, Rebecca; Rawlins, Gilda; du Plessis, Wencke
Case summary: A 1-year-old, female spayed, domestic shorthair, indoor cat on the island of St Kitts was diagnosed with platynosomiasis, infection with a feline-specific liver fluke, and treated with praziquantel at the marketed dose for tapeworms (5 mg/kg; actual calculated dose 5.75 mg/kg). Serial fecal analyses showed that egg counts decreased to zero within 10 days of treatment but re-emerged at day 17 and persisted at low levels until a second treatment was administered on day 78. After the second treatment, all fecal samples (n = 15) from day 85 to day 350 post-initial treatment were negative for Platynosomum ova. Relevance and novel information: Treatment of platynosomiasis is poorly documented; no drugs are labeled for use against Platynosomum and the efficacy of suggested treatments is unknown. Using 5.75 mg/kg once, a dose that is significantly lower than published recommended doses for platynosomiasis, egg counts initially disappeared but re-emerged and persisted at low levels until a second treatment was administered. We hypothesize that immature forms may not have been killed and subsequently matured to produce eggs, or that the one-time dose may not have been completely effective at eliminating all adult flukes. However, administering praziquantel at 5.75 mg/kg twice, several weeks apart, appeared to be effective in treating this cat with platynosomiasis, as evidenced by monitoring of fecal egg counts over the course of 350 days.